2008
DOI: 10.1007/s11605-007-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Surgery for Primary Gastrointestinal Tract Melanoma

Abstract: PGIM occurs most often in the oral-nasopharynx and anal canal. Surgical extirpation is the only identifiable treatment modality that significantly improves survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 28 publications
(33 reference statements)
4
127
1
7
Order By: Relevance
“…Kimura et al (17) reported the use of endoscopic mucosal resection for the treatment of early PMME, and recorded no recurrence after 18 months. Consistent with this finding, Cheung et al (18) evaluated the Surveillance, Epidemiology and End Results database of primary and identified complete surgical resection as the only identifiable treatment strategy that significantly improved survival in PMME patients. Therefore, the present study proposes that the timely surgery received by the current patient was significantly associated with the outcome, as the patient remained in good condition 12 months after esophagectomy.…”
Section: Discussionmentioning
confidence: 79%
“…Kimura et al (17) reported the use of endoscopic mucosal resection for the treatment of early PMME, and recorded no recurrence after 18 months. Consistent with this finding, Cheung et al (18) evaluated the Surveillance, Epidemiology and End Results database of primary and identified complete surgical resection as the only identifiable treatment strategy that significantly improved survival in PMME patients. Therefore, the present study proposes that the timely surgery received by the current patient was significantly associated with the outcome, as the patient remained in good condition 12 months after esophagectomy.…”
Section: Discussionmentioning
confidence: 79%
“…In a review article, Chang et al analyzed 84,836 cases of melanoma (in the USA) recorded in the period from 1985 to 1994 and localized in the skin (91.2%), eyes (5.2%), mucosa (1.2%), and unknown primary localization (2.2%) ( Table 1) 26 . In the study by Cheung et al, there were 659 cases of melanoma of the gastrointestinal tract: 53.6% anorectal (anal 31.4%, and rectal 22.2%), 32.8% oropharyngeal, 5.9% esophageal, 2.7% of the stomach, 2.3% of the small intestine, 1.4% of the gallbladder, and 0.9% of the colon 27 . In the review article by Hicks and Flaitz, aggregated data are given from several articles related to melanomas of the mucosa of the head and neck, which include 703 cases of oral mucosa and 770 cases of sinonasal mucosa (Table 2) 4,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Th ey are a sign of already advanced melanoma, and are often accompanied by metastases to cervical lymph nodes. Melanomas of the oral cavity are located in 80% of cases on the mucosa of the palate and gingiva, and in other parts of the oral cavity, e.g., buccal mucosa, lips, tongue, base of the mouth, and uvula in 20% of cases 4,26,27 . From 35% to 37% of patients in whom OM develops, have pre-existing benign melanomatosis of the oral mucosa 28 .…”
Section: Characteristics Of Oral Melanomasmentioning
confidence: 99%
“…The data collected from large cancer registries provides insight into tumor behavior and allow us to examine outcomes from current treatment strategies. [13][14][15][16][17][18] Although this represents an excellent database for comparative outcomes analysis, it is not without limitations. Using area poverty as a proxy for SES may result in misclassification of some patients whose postal code does not accurately reflect the true income level of the individual.…”
Section: Discussionmentioning
confidence: 99%